AUTOMATED HOTEL CHECK-IN SERTA DAMPAKNYA PADA TENAGA KERJA LOKAL - Ni Gusti Nyoman Suci Murni; Made Ruki; I.A. Kade Werdika Damayanti (Politeknik Negeri Bali, 2017)
The tourism sector is one of the most heavily influenced sectors of information technology. Hotels that are a component of tourism cannot be separated from these influences, especially in information services, room reservations, check-in / check-out service, and other services. With the sophistication of information technology, everyone can access any information, from anywhere; at a very cheap price even every country provides free facilities for that purpose. This study uses qualitative methods where the data source obtained by looking for some libraries related to self check-in. The results show that there are some differences that applied between the check-in manual and self check-in, and the impact caused by the application of self check-in. The positive impact of self check-in are speeding up the check-in process, saving payrolls, simplifying services, simplifying reporting, and saving time. While the negative impacts such as reducing employment in developing countries, reducing social communication / human touch, reducing the understanding of cross cultural understanding, allowing the occurrence of crime (cyber crime) as well as very expensive initial cost.